The Effects of a Mindfulness Program on Mental Health in Students at an Undergraduate Program for Teacher Education: A Randomized Controlled Trial in Real-Life - Juul, Lise; Brorsen, Eva; Gøtzsche, Katinka; Nielsen, Birgitte Lund; Fjorback, Lone Overby (Frontiers in Psychology, 2021)
Background: In this study, we aimed to investigate the effects of a mindfulness program including Mindfulness-Based Stress Reduction (MBSR) on the mental health of student teachers when offered at their educational institution in a real-life context. Methods: A parallel randomized controlled trial (RCT) was conducted among self-selected student teachers at a Danish undergraduate program for teacher education in the autumns of 2019 and 2020. Participation was not recommended in case of (1) clinical depression or a diagnosis of psychosis or schizophrenia, (2) abuse of alcohol, drugs, and/or medicine. Randomization was performed by a Statistician who was blinded to the identity of the students. Data was collected using self-reported questionnaires. The primary outcome was a change in perceived stress 3 months from baseline. Secondary outcome measures were symptoms of anxiety and depression, well-being, resilience, mindfulness, and thoughts and feelings during rest. The effects were analyzed according to the intention-to-treat principle using mixed-effect linear regression models. Mediating effects of mindfulness skills on the mental health outcomes were explored using structural equation modeling. Results: The study group included 67 student teachers with 34 allocated to the intervention group (median age: 25 years; women: n = 24, 71%); and 33 students (median age: 25 years; women: n = 25, 76%) allocated to a waiting list control group. At baseline, mean Perceived Stress Scale (PSS) scores were 18.88 (SD: 5.75) in the intervention group and 17.91 (SD: 6.36) in the waiting list control group. A total of 56 students completed the questionnaire at a 3-month follow-up (28 in both the intervention- and the control group). Statistically significant effects of the intervention were found on perceived stress, symptoms of anxiety and depression, well-being, and on three of seven resting-state dimensions. No effects were found on resilience or mindfulness. Statistically significant mediated effects via resting-state dimensions were found. Conclusion The findings suggested that offering a mindfulness program at an undergraduate program for teacher education could significantly improve the mental health among self-selected students within 3 months. Results of mediation analysis supported the hypothesis that some of the effects might be explained by reduced distracting thoughts. Clinical Trial Registration: [www.ClinicalTrials.gov], identifier [NCT04558099].